Functionalized 2D materials F–MoS2 and F-g-C3N4 with TiO2 as Composite Electrocatalysts for Electrochemical Hydrogen Evolution. (15th February 2023) - Shwetharani, R.; Pratheeksha, M.; Sumanth Dongre, S.; Geetha Balakrishna, R.
Abstract: Electrochemical hydrogen evolution is an important research field to produce renewable energy. Nanostructured two dimensional (2D) materials such as g-C3 N4 and MoS2 are potential electrocatalysts for hydrogen evolution reaction (HER). The incorporation of semiconducting material into 2D material enhances the hydrogen evolution. Here in, we have developed composite of acid functionalized MoS2 and g-C3 N4 with TiO2 (F–MoS2 /TiO2, F-g-C3 N4 /TiO2 ). The F–MoS2 /TiO2 composite exhibited excellent electrochemical HER activity with an overpotential of 103 mV Vs RHE at 20 mA/cm 2 compared to pristine F–MoS2 of 232 mV, TiO2 of 455 mV V s RHE. In addition F-g-C3 N4 /TiO2 showed high overpotential of 322 mV at 5 mA/cm 2 than pristine F-g-C3 N4 and TiO2 of 433 mV and 448 mV V s RHE at 2.7 mA/cm 2 respectively. Highlights: Composite of acid functionalized MoS2 and g-C3 N4 with TiO2 through hydrothermal process. The F–MoS2 /TiO2 exhibited excellent HER activity with an overpotential of 103 mV at 20 mA/cm 2 . In addition F-g-C3 N4 /TiO2 showed high overpotential of 322 mV at 5 mA/cm 2 than pristine F-g-C3 N4 and TiO2 . The 2D materials with Li intercalation leading to increase in interlayer spacing can reduce diffusion energy barrier. Acid-functionalization of 2D nanosheets leads to enhanced charge transport between substrate and electrode material.